2018
DOI: 10.19082/6843
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the perception of women with epilepsy about pregnancy concerns: a qualitative study

Abstract: Background and aimEpilepsy is a common neurological disorder in pregnancy, which is associated with increased maternal and fetal adverse outcomes. This study aimed to explore the reproductive healthcare needs of women with epilepsy before, during and after childbirth.MethodsThis was a qualitative study using a content analysis method. The study population was marital women with epilepsy in reproductive age (15–45 years) referred to Imam Hossein Hospital, Tehran, Iran. Participants were 16 women chosen using pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…One of the important findings of our review was that none of the women received support from healthcare professionals on how to provide care for the baby and that they were left alone. In the literature, it was determined that mothers with chronic diseases (Epilepsy, Crohn’s disease, inflammatory bowel disease) similarly felt unprepared for and uninformed about the postpartum period, had poor communication with healthcare professionals, did not receive enough support, and experienced a sense of abandonment during this period (Atarodi-Kashani et al, 2018; Hansen et al, 2022; Julsgaard et al, 2014; Kimura & Ohmori, 2015; Weckesser & Denny, 2013). These findings clearly demonstrate how important postpartum support is for women with chronic diseases such as MS. Healthcare professionals should organize home visits in the postpartum period, individualized care should be planned for the mother and baby and counseling should be given, considering the disability of women with MS.…”
Section: Discussionmentioning
confidence: 99%
“…One of the important findings of our review was that none of the women received support from healthcare professionals on how to provide care for the baby and that they were left alone. In the literature, it was determined that mothers with chronic diseases (Epilepsy, Crohn’s disease, inflammatory bowel disease) similarly felt unprepared for and uninformed about the postpartum period, had poor communication with healthcare professionals, did not receive enough support, and experienced a sense of abandonment during this period (Atarodi-Kashani et al, 2018; Hansen et al, 2022; Julsgaard et al, 2014; Kimura & Ohmori, 2015; Weckesser & Denny, 2013). These findings clearly demonstrate how important postpartum support is for women with chronic diseases such as MS. Healthcare professionals should organize home visits in the postpartum period, individualized care should be planned for the mother and baby and counseling should be given, considering the disability of women with MS.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study from Iran have suggested that WwE were doubtful about breastfeeding the child after being educated and their concerns were exacerbated by the physician's inconsistent perspective about breastfeeding. 19 Nine participants (33.3%) have expressed concern about having AEDs and dose adjustments of AEDs (11.1%) during pregnancy. A qualitative study from Norway has revealed that dose adjustments of AEDs were a major concern for the pregnant WWE.…”
Section: Discussionmentioning
confidence: 99%
“…20 A recent content analysis qualitative study from Iran has advised that drug dose alteration was the anxiety-provoking factor among WwE during pregnancy. 19 A Korean study with the inclusion of 186 WwE has stated that regardless of medical suggestion 58% of WwE were in view of terminating AEDs during an imminent pregnancy, and 25% of WwE were chosen to have fewer children due to their epilepsy. 21,22 Low level pregnancyrelated knowledge was connected with the choice to suspend the AEDs during a future pregnancy and an overstated insight of the children's risk for developing epilepsy was related to have fewer children.…”
Section: Discussionmentioning
confidence: 99%
“…32 Pregnant women with epilepsy are especially vulnerable, with one-quarter of women with epilepsy suffering from chronic postpartum depression. 33 The difficulties these women confront postpartum may correlate to a decline in mental health workers and neurologists. 34 According to research conducted by the World Health Organization (WHO), 35 epilepsy specialists provide individualized healthcare to individuals resident in 89% of HICs, as opposed to just 56% of LMICs.…”
Section: Limited Access To Skilled Professionals and Coordinated Carementioning
confidence: 99%
“…32 Pregnant women with epilepsy are especially vulnerable, with one-quarter of women with epilepsy suffering from chronic postpartum depression. 33 The difficulties these women confront postpartum may correlate to a decline in mental health workers and neurologists. 34…”
Section: Management Gaps Of Neurological Disorders In Pregnant Women ...mentioning
confidence: 99%